Marxism After Polanyi - Burawoy, Michael (Marxisms in the 21st Century: Crisis, Critique and Struggle, 2013)
KM - What should we do with Marxism ? For most the answer is simple. Bury it ! Mainstream social science has long since bid farewell to Marxism. The approach adopted here is that Marxism is a living tradition that enjoys renewal and reconstruction as the world it describes and seeks to transform undergoes change ... However, Marxsm cannot simply mirror the world. It seeks to change the world, but changing such a variegated world requires a variegated theory that keeps up with the times and accommodates places.
Sociology
Keywords: MARX; Karl; 1818-1883; Marxism; fictitious commodities

Port of trade - Möller, Astrid (The Encyclopedia of Ancient History, 2013)
A “port of trade” is a theoretical concept developed by Karl Polanyi (1886–1964) to describe the phenomenon of a particular kind of trading post.
History
Keywords: anthropology; economic history; multiculturalism